AN AUDIT OF THE MANAGEMENT OF EPILEPSY IN CHILDREN AND YOUNG PEOPLE WITH INTELLECTUAL DISABILITIES. Issue 9 (13th August 2015) - Liew, Ashley
Abstract : Objective: To assess the management of epilepsy in children and young people with intellectual disabilities, against quality standards published by the National Institute for Health and Care Excellence (NICE) and the International League against Epilepsy (ILAE). Method: 276 case notes from a large CAMHS Learning Disabilities service were audited to identify patients with a current diagnosis of epilepsy. Data collected included: (a) demographics, (b) epilepsy type, (c) seizure control, (d) prescribed medication, (e) professionals involved, and (f) psychiatric diagnoses. Descriptive statistics were computed. Results: 38 patients from the service were identified as having epilepsy. 21 (55%) patients were of male gender. The predominant seizure type was focal seizures affecting 26 patients (68%). 28 (74%) patients were on 1 anti-epileptic medication, but notably there were 6 (16%) patients on 3 or more anti-epileptic medications. 26 (68%) patients had more than 1 psychiatric diagnosis, and 34 (89%) patients were prescribed psychotropic medication. 24 (63%) patients were reviewed regularly by a Paediatric Neurologist. It was unclear which professional was reviewing the epilepsy management in 2 (5%) patients. 4 (11%) patients had a joint Neurology and Psychiatry review within the last 12 months. Conclusion: Children and young people with intellectual disabilities have higher rates of epilepsy compared to the general population. The nature of their epilepsy tends to be more difficult to diagnose and treat. Despite both NICE and ILAE guidelines recommending that care be delivered for this group of patients in a tertiary neurology centre, preferably with joint management between a neurologist and psychiatrist; this was a rarity in the audited population. Several actions are proposed to improve the quality of epilepsy care in this group of patients.